Upaya Meningkatkan Kemampuan Guru dalam Pembelajaran Berbasis Manajemen Iklim Budaya Sekolah di SDN 1 Padalarang Kabupaten Bandung Barat - Ayi Najmul Hidayat; Kingking Muttaqien; Gatot Yusuf Effendi (LPPM UNINUS, 2018)
This training is purposed for teachers at Elementary School 1 Padalarang West Bandung to improve the ability in learning based on school and culture climate management. The methods used in this training are discussion, lectures and demonstration/practices. The training results show that the trainees responded positively to the school and culture climate management in learning. They were also motivated to join the training and to follow incoming trainings as well as to try applying the learning based on school and culture climate management. The training reveals many abilities, advantages, and experiences to the trainees so that many participated and contributed over the implementation. Trainees are listening, scrutinizing and critiquing training materials. The impact of the training outcomes is training participants increased their ability and proved their confidence and understanding to the spirit of applying the results to their daily life.